Synthesis and properties of new materials with cobalt(II), iron(III) and manganese(III)-substituted Keggin polyoxotungstates and 1-alkyl-3-methylimidazolium cations - Santos, Filipe M.
Several novel compounds with 1-alkyl-3-methylimidazolium cations (alkyl = butyl and octyl) and first row transition metal-substituted Keggin polyoxoanions were synthesised, having the general formula (cation)(m)[PW11O39M(H2O)]center dot xH(2)O or (cation)(m-1)H[PW11O39M(H2O)]center dot xH(2)O, M = Co, Fe, Mn and m = anion charge. All compounds were characterized by spectroscopic and analytical techniques. These studies indicated that both the polyoxometalates and the cations are present in the solids without major alterations. Cyclic voltammetry studies were performed for compounds with 1-butyl-3-methylimidazolium. Disregarding the loss of crystallization or coordinated water, the compounds were found to be stable up to near 300 degrees C. The onset of the decomposition of the organic cations, as determined by thermogravimetry, occurred in the 300-350 degrees C range. The metal-substituted polyoxoanions are stable up to around 300 degrees C, but after this temperature the anions transform into the parent [PW12O40](3-) anion, with loss of the substituting metal. Final decomposition to a mixture of oxides occurred only above 600 degrees C. It was also possible to obtain the crystalline compounds Na2K(Bmim)(2)[PW11O39Co(H2O)]center dot 7.5H(2)O and Na(Bmim)(4)[PW11O39Co(H2O)]center dot 2H(2)O and determine their structures by single crystal X-ray diffraction. Compounds with substituted imidazolium cations and metal-substituted polyoxometalates are expected to present a set of properties that make them interesting in many fields, like catalysis. This study aimed at contributing to the understanding the effect of altering the substituting metal and the counter-cation in the properties of this type of compounds. (C) 2015 Elsevier Ltd. All rights reserved.